2024
DOI: 10.18063/ijb.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Concentric bioprinting of alginate-based tubular constructs using multi-nozzle extrusion-based technique

Abstract: Abstract:Bioprinting is a layer-by-layer additive fabrication technique for making three-dimensional (3D) tissue and organ constructs using biological products. The capability to fabricate 3D tubular structure in free-form or vertical configuration is the first step towards the possibility of organ printing in three dimensions. In this study, alginate-based tubular structures of varying viscosity were printed vertically using multi-nozzle extrusion-based technique. Manufacturing challenges associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 40 publications
(38 reference statements)
0
76
0
Order By: Relevance
“…Three-dimensional (3D) bio-printing technology is emerging as a novel and useful technique for complex 3D biomimetic architectures creation in order to enhance tissue repair of skin, heart, bone, and retina and so forth. [1][2][3][4][5][6] The biomimetic architectures can mimic the natural state of organ that is providing correct extracellular matrix (ECM) compositions, localization and biological functions for the cells during in vivo study compared to the conventional 2D and 3D culturing techniques, thus they further enhance cellular differentiation, gene expressions, proliferation, migration and cell material interactions and so forth. 7,8 The bio-printing technology can be subdivided into inkjet printing, extrusion, microvalve based printing and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional (3D) bio-printing technology is emerging as a novel and useful technique for complex 3D biomimetic architectures creation in order to enhance tissue repair of skin, heart, bone, and retina and so forth. [1][2][3][4][5][6] The biomimetic architectures can mimic the natural state of organ that is providing correct extracellular matrix (ECM) compositions, localization and biological functions for the cells during in vivo study compared to the conventional 2D and 3D culturing techniques, thus they further enhance cellular differentiation, gene expressions, proliferation, migration and cell material interactions and so forth. 7,8 The bio-printing technology can be subdivided into inkjet printing, extrusion, microvalve based printing and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Microneedle, tapered tip, or nozzle based syringe extrusion methods were widely applied in the reported extrusion-based bioprinting approaches7124344. We herein found that the micropipette-based extrusion method is a good approach to print tightly packed PLGA microspheres.…”
Section: Discussionmentioning
confidence: 82%
“…The layer thickness can be affected by other printing parameters such as printing path height, path space and nozzle diameters . Printing numerous layers in the z direction will affect the overall structure and deviates from the intended build …”
Section: Design Factors and The Capabilities Of Bioprintingmentioning
confidence: 99%
“…Materials or bio‐inks formulations are optimized to achieve desired viscosity, yield stress and mechanical integrity for fast shear recovery during and after printing . Some methods of optimization for direct printing includes forming semi‐crosslinked mixture and adding thickening agent . Adding enzyme crosslinker, adjusting temperature of thermosensitive hydrogel, and pre‐exposure of photopolymer to UV light are some methods to improve viscosity of bio‐ink through partially crosslinking the hydrogel.…”
Section: Bioprinting Fabrication Strategiesmentioning
confidence: 99%
See 1 more Smart Citation